PENDAPATAN USAHATANI PEMBENIHAN LELE DUMBO DAN LELE SANGKURIANG DI DESA BABAKAN, KECAMATAN CISEENG, BOGOR - Putri Amalia; Ratna Winandi Asmarantaka (Magister Science of Agribusiness, Department of Agribusiness, FEM-IPB University, 2015)
Catfish is one of the nine potential leading commodities in Indonesia. The biggest demand of the fish reaches 250 tons a day in Java and this makes the fish breeding business very important. One of the catfish breeding areas is Babakan Seeng, Bogor District. There are two catfish verieties, i.e Dumbo, which is cultivated in Pokdakan Jumbo Lestari and Sangkuriang in Pokdakan kubang sejahtera. The breeding system of those varieties is different: stocking density of 10 000 juveniles per 300 m2 for Dumbo and 20 000 juveniles per 300 m2 for Sangkuriang, due to the bigger egg hatching expectation; i.e 90%. The research showed that the income of Dumbo catfish farm was Rp 7 544 531, while that of the sangkuriang catfish farm was only Rp 3 857 981. R/C ratio of Dumbo catfish farm was 1.49 and R/C ratio of Sangkuriang catfish farm was 1.16. Chi-squares analysis also proves that the difference the way aquaculture can effect farm income. This proves that Dumbo catfish farm is more profitable compared to Sangkuriang farm. Sangkuriang catfish hatchery can be more profitable when the stocking density is lessened.